HANDS-ON – FUNCTIONAL CHEESE BREAD WITH ELDERLY RESIDENTS IN A LONG-TERM CARE INSTITUTION: AN EXPERIENCE REPORT FAP - Fernandes Pinheiro, Debora; Lunelli Moro, Ana Claudia; do Nascimento Cardoso, Simone; Azeredo Silva, Carolina; Rezende Adami, Eliana (Extensão em Foco (ISSN: 2317-9791), 2024)
Nursing homes for the elderly play a crucial role in the lives of many individuals at a certain stage of their life cycle, improving their quality of life during that phase. Recognizing this importance, this work aimed to develop workshops involving both students and teachers, aimed at elderly people living in institutions, with the intention of promoting their autonomy and well-being. The workshops were designed in a multidisciplinary way and were applied on a fortnightly basis in an institution located in the mid-west of Santa Catarina. They included culinary activities and the application of a nutritional questionnaire to assess the health of residents and contributed significantly to the quality of life of institutionalized elderly people.